The Public Establishment as an Example of an Institution of Administrative Law in Constant Evolution (Contemporary Central & East European Law, 2024)
The functioning of public establishments has been a topic of significant interest in administrative law doctrine for several decades. This institution of administrative law is typical of continental systems and is rooted in both Western traditions (such as French and German law) and the legal systems of former communist countries. This study presents the basic issues related to public establishments, including a historical and comparative legal outline and their characteristics. Particular attention will be paid to the contemporary understanding of the concepts of establishment relationship and establishment authority. Additionally, the basic research dilemmas in this area will be examined from the perspective of the 2020s. The article concludes with a summary.